Response surface methodology: an emphatic tool for optimized biodiesel production using rice bran and sunflower oils - Mumtaz, Muhammad Waseem; Adnan, Ahmad; Anwar, Farooq; Mukhtar, Hamid; Raza, Muhammad Asam; Ahmad, Farooq; Rashid, Umer (MDPI, 2012)
The current study describes the emphatic use of response surface methodology for the optimized biodiesel production using chemical and enzymatic transesterification of rice bran and sunflower oils. Optimal biodiesel yields were determined to be 65.3 ± 2.0%, 73.4 ± 3.5%, 96.5 ± 1.6%, 89.3 ± 2.0% and 41.7 ± 3.9% for rice bran oil and 65.6 ± 1.2%, 82.1 ± 1.7%, 92.5 ± 2.8%, 72.6 ± 1.6% and 50.4 ± 2.5% for sunflower oil via the transesterification catalyzed by NaOH, KOH and NaOCH3,NOVOZYME-435 and A.n. Lipase, respectively. Based upon analysis of variance (ANOVA) and Response Surface plots significant impact of reaction parameters under study was ascertained. FTIR spectroscopic and HPLC methods were employed for monitoring the transesterification reaction progress while GC-MS analysis was performed to evaluate the compositional analysis of biodiesel. The fuel properties of both the rice bran and sunflower oil based biodiesel were shown to be technically compatible with the ASTM D6751 and EN 14214 standards. The monitoring of exhaust emission of synthesized biodiesels and their blends revealed a marked reduction in carbon monoxide (CO) and particulate matter (PM) levels, whereas an irregular trend was observed for NOx emissions.